Health communication from theory to practice - Schiavo, Renata (Jossey-bass public health)
"Now in its second edition, Health Communication: From Theory to Practice provides a comprehensive introduction to theory, intervention design, current issues, and special topics in health communication. The book also represents a hands-on guide to program development, implementation, and evaluation. This second edition further emphasizes the importance of a people-centered and participatory approach to health communication interventions, which takes into account key social determinants of health as well as the interconnection of various health and social fields. While maintaining a strong focus on the importance of behavioral, social, and organizational results as key outcomes of health communication interventions, this second edition also includes new or updated information, theoretical models, resources, and case studies on health equity, urban health, new media, emergency and risk communication, strategic partnerships in health communication, policy communication and public advocacy, cultural competence, health literacy, and the evaluation of health communication interventions"--Provided by publisher.